1995
DOI: 10.1002/pssa.2211510225
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties and electric conductivity of dimethylammonium tetrachlorcobaltate ferroelectric crystals

Abstract: The dielectric parameters and electric conductivity of (NH2(CH3)2)2CoCl4 crystals are investigated. Existence of the ferroelectric phase was observed below Tc = 258 K. The occurrence of phase transitions at 244, 314, and 435 K is confirmed. The investigated crystals also manifest anomalously high conductivity commensurate with that in semiconductors. Its value as well as region of existence strongly depend on the preceding history of the sample. It is shown that the anomalous conductivity is connected with tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 9 publications
2
29
1
1
Order By: Relevance
“…Unfortunately, it is difficult to investigate in detail the dielectric relaxation process because of very narrow region of existence of phase II. Nevertheless, one can note that determined value of Ea is higher than in related compounds with alkylammonium-cation (Ea = 0.340 eV for (NH2(CH3)2)2CoCl4 [9] and Ea = 0.355 eV for NH2(CH3)2MnCl3 •2H20 [8]), first of all, due to larger energy barrier between two different H-bonds [2].…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Unfortunately, it is difficult to investigate in detail the dielectric relaxation process because of very narrow region of existence of phase II. Nevertheless, one can note that determined value of Ea is higher than in related compounds with alkylammonium-cation (Ea = 0.340 eV for (NH2(CH3)2)2CoCl4 [9] and Ea = 0.355 eV for NH2(CH3)2MnCl3 •2H20 [8]), first of all, due to larger energy barrier between two different H-bonds [2].…”
Section: Resultsmentioning
confidence: 71%
“…The temperature dependence of a manifests clear anomalies at the temperatures limiting mentioned phase (with accounting of the temperature hysteresis). One can note that observed comparatively high conductivity by their value even exceeds the conductivity in known protonic conductor such as (NH2(CH3)2)2CoCl4 [9].…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition to their technological importance in numerous electrochemical devices, such as fuel cells and chemical sensors [4], these materials provide good models for transport in biological systems [5]. Among these materials are compounds of the type [(CH 3 ) 4 X-ray diffraction studies showed that the tetramethylammonium salts [(CH 3 ) 4 N] 2 MX 4 , and tetramethylphosphonium salts, [(CH 3 ) 4 P] 2 MX 4 , are isostructural with the P121/c1 phase at room temperature [6,7]. The room temperature structure of [(CH 3 ) 4 Z] 2 MX 4 where Z = As and/or P and M = Co 2+ or Zn +2 [8][9][10], consists of alternating layers of tetrahedral [(CH 3 ) 4 +2 and Pb +2 and X = Cl was synthesized [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Among these materials are compounds of the type [(CH 3 ) 4 X-ray diffraction studies showed that the tetramethylammonium salts [(CH 3 ) 4 N] 2 MX 4 , and tetramethylphosphonium salts, [(CH 3 ) 4 P] 2 MX 4 , are isostructural with the P121/c1 phase at room temperature [6,7]. The room temperature structure of [(CH 3 ) 4 Z] 2 MX 4 where Z = As and/or P and M = Co 2+ or Zn +2 [8][9][10], consists of alternating layers of tetrahedral [(CH 3 ) 4 +2 and Pb +2 and X = Cl was synthesized [11][12]. The electric properties of the Mn +2 and Cu +2 salts indicated the presence of structural phase transitions at 378 K and 411 K for the Cu +2 and at 368 K for the Mn +2 salts [11,12].…”
Section: Introductionmentioning
confidence: 99%